Is My MOOC Learner-Centric? A Framework for Formative Evaluation of MOOC Pedagogy - Shah, Veenita; Murthy, Sahana; Iyer, Sridhar (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
MOOCs popularly support the diverse learning needs of participants across the globe. However, literature suggests well-known scepticism regarding MOOC pedagogy which questions the effectiveness of the educational experience offered by it. One way to ensure the quality of MOOCs is through systematic evaluation of its pedagogy with the goal to improve over time. Most existing MOOCs’ quality evaluation methods do not account for the increasing significance of learner-centric pedagogy towards providing a richer learning experience. This paper presents a MOOC evaluation framework (MEF), designed with a strong pedagogical basis underpinned by theory and MOOC design practices, which evaluates the integration of learner-centric pedagogy in MOOCs. Using mixed-methods research, the internal validation was conducted through expert reviews (N = 2), and external validation (N = 13) was conducted in the field to test model usability and usefulness. The framework was classified as “good” (SUS: 78.46) in terms of usability. A high perception of usefulness (84%–92%) was observed for the framework as a formative evaluation tool for assessing the integration of learner-centric pedagogy and bringing a positive change in MOOC design. Different participants acknowledged new learning from varied dimensions of the framework. Participants also recognized that the scores obtained using the MEF truly reflected the efforts taken to incorporate learner-centric design strategies in the evaluated dimensions. The framework focuses on learner-centric evaluation of MOOC design with a goal to facilitate improved pedagogy.